157k views
3 votes
Simplify the expression below.5 + 3 • 2 - 4^2 • -2

Simplify the expression below.5 + 3 • 2 - 4^2 • -2-example-1

1 Answer

7 votes

To simplify the expression, we follow GEMDAS. We start with grouping symbols (there's none here), followed by exponents, then multiplication or division, and finally, addition or subtraction.


\begin{gathered} 5+3\cdot2-4^2\cdot-2 \\ \\ =5+3\cdot2-16\cdot-2 \\ \\ =5+6-(-32) \\ \\ =11+32 \\ \\ =43 \end{gathered}

The answer is 43.

User Bishoy Kamel
by
5.0k points